Sub Bottom Profiler Data Analysis to Identify the Thickness of Sediments (Study Case: Alur Pelayaran Timur Surabaya) - M. Dwiki Amirullah; Khomsin Khomsin; Danar Guruh Pratomo (Institut Teknologi Sepuluh Nopember, 2019)
One of the acoustic instruments were used for the measurement of the seabed is the Sub Bottom Profiler. This instrument uses a low-frequency acoustic signal which has the ability to penetrate the layers of the ocean bottom up to a depth of several meters. The purpose of the survey using the Sub Bottom Profiler that is to conduct the investigation and identification of coating the ocean floor so that the retrieved information related to seabed stratigraphy. The location of research are on Alur Pelayaran Timur Surabaya. Secondary data is Raw data Sub bottom profiler, RAW data of single beam, SVP and tide data has been processed. The data retrieved from the District Navigasi kelas 1 Surabaya. The location of the research is classified as waters of the shallow waters. There are three layers of sediment. The pattern of seismic reflection data are parallel and subparallel. Thickness between the base of the sea surface with the first layer has a constituent sediments form the sandy mud. Thickness of the layer of sediment volume values the greatest there is between the first and second layers of 8.009.815.18 m³. The total volume of the thickness of the layer sediment 17,945,928.40 m³.